Anti-amphiphysin antibody-induced paraneoplastic-autoimmune encephalitis: case report and literature review - E. Kavaliauskaitė; R. Mameniškienė (Neurologijos seminarai)
Anti-amphiphysin antibody-induced encephalitis is an immune-mediated inflammatory disease of the brain caused by onconeuronal antibodies. Amphiphysin antibodies are associated with various paraneoplastic neurological syndromes and tumours. The absence of a particular clinical pattern and pathognomonic features makes diagnosing paraneoplastic-autoimmune encephalitis complicated, especially when a malignancy is not initially apparent. Detection of specific antibodies in serum and cerebrospinal fluid remains the main diagnostic tool. Up to this date, no cases with epileptic seizures as one of the clinical manifestations of anti-amphiphysin encephalitis have been reported. In this article, we present a rare clinical case of a 54-year-old man diagnosed with autoimmune-paraneoplastic encephalitis caused by antibodies against amphiphysin which manifested with atypical clinical symptoms such as epileptic seizures, visual and perception impairment, paraesthesia, and elevated CSF protein levels with no detectable tumour.